A first view on the unsuspected intragenus diversity of N‐glycans in Chlorella microalgae. (17th March 2020) - Mócsai, Réka; Figl, Rudolf; Sützl, Leander; Fluch, Silvia; Altmann, Friedrich
Summary: Chlorella microalgae are increasingly used for various purposes such as fatty acid production, wastewater processing, or as health‐promoting food supplements. A mass spectrometry‐based survey of N‐glycan structures of strain collection specimens and 80 commercial Chlorella products revealed a hitherto unseen intragenus diversity of N‐glycan structures. Differing numbers of methyl groups, pentoses, deoxyhexoses, and N ‐acetylglucosamine culminated in c. 100 different glycan masses. Thirteen clearly discernible glycan‐type groups were identified. Unexpected features included the occurrence of arabinose, of different and rare types of monosaccharide methylation (e.g. 4‐ O ‐methyl‐ N ‐acetylglucosamine), and substitution of the second N ‐acetylglucosamine. Analysis of barcode ITS1–5.8S–ITS2 rDNA sequences established a phylogenetic tree that essentially went hand in hand with the grouping obtained by glycan patterns. This brief prelude to microalgal N‐glycans revealed a fabulous wealth of undescribed structural features that finely differentiated Chlorella ‐like microalgae, which are notoriously poor in morphological attributes. In light of the almost identical N‐glycan structural features that exist within vertebrates or land plants, the herein discovered diversity is astonishing and argues for a selection pressure only explicable by a fundamental functional role of these glycans. Significance Statement: The protein N‐glycosylation machinery of green algae has hitherto been considered as being essentially similar to that of land plants. The current work reveals a plethora of yet unknown N‐glycan structures only within the Chlorella clade – an economically relevant branch – with considerable repercussions on taxonomy and functional significance.